Pengaruh Metode Dakwah Digital, Interaksi Teman Sebaya, dan Pengawasan Orang Tua Terhadap Penguatan Karakter Islami Peserta Didik di SMKN 1 Bone - Febriani, Iva; Arisal A; Kasmah (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Strengthening students' Islamic character is a crucial challenge in the digital era because the development of information technology influences adolescents' mindsets, attitudes, and behavior. Therefore, synergy is needed between the use of digital da'wah media, peer environments, and parental supervision to support Islamic character formation. This study aims to analyze the influence of digital da'wah methods, peer interactions, and parental supervision on strengthening students' Islamic character at SMKN 1 Bone. The study used a quantitative approach with an explanatory research design. The study sample consisted of 298 students selected using proportionate stratified random sampling. Data were collected through questionnaires and documentation, then analyzed using multiple linear regression. The results showed that digital da'wah methods, peer interactions, and parental supervision simultaneously had a significant effect on strengthening students' Islamic character (p < 0.05). The coefficient of determination (R² = 0.59) indicates that these three variables were able to explain 59% of the variation in strengthening Islamic character, while 41% was influenced by other factors outside the research model. These findings confirm that strengthening Islamic character requires collaboration between the appropriate use of digital da'wah, a positive social environment, and ongoing parental supervision.